Natural Gas Consumption of Emerging Economies in the Industrialization Process - Chai, Jian; Liang, Ting; Zhou, Xiaoyang; Ye, Yunxiao; Xing, Limin; Lai, Kin (Sustainability, 2016)
Natural gas has become more and more important in the world energy market with the change of energy consumption structure and consumption subjects. This paper applies the panel smooth transition regression (PSTR) model to study the nonlinear relationship between natural gas consumption and economic variables of emerging economies, and the empirical results show that: (1) There is a non-linear relationship among natural gas consumption, GDP per capita, industrialization and urbanization rate; (2) The optimal PSTR model is a two-regime model by using the lagged industrialization as a transition variable, and the impact of GDP per capita and of industrialization on natural gas consumption shows incomplete symmetry in low and high regime, respectively; (3) The result of time-varying elasticity analysis indicates that natural gas consumption is inelastic to GDP per capita, but elastic to both industrialization and urbanization. The elasticity of GDP per capita generally decrease with fluctuation, the elasticity of industrialization tends to rise, and the elasticity of urbanization is linear at high level; (4) Regional difference shows that there are 10 emerging economies are in first regime (below industrialization of 43.2%), and the remaining 6 are in second regime. This provides reference for countries in different transformation periods to make economic policies adapting to energy saving, energy structure optimization and other sustainable development strategies.